2021
DOI: 10.1371/journal.pone.0248934
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of hypertension among adults: A community based study in Addis Ababa, Ethiopia

Abstract: Background In all areas of the World Health Organization, the prevalence of hypertension was highest in Africa. High blood pressure is a significant risk factor for coronary and ischemic diseases, as well as hemorrhagic stroke. However, there were scarce data concerning the magnitude and risk factors of hypertension. Thus, this study aimed to identify the prevalence and associated factors of hypertension among adults in Addis Ababa city. Method A community-based cross-sectional study was conducted from June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
28
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 21 publications
10
28
0
5
Order By: Relevance
“…Individuals aged 45-54 years, 55-64 years, and ≥65 years were 4.63, 14.40, and 19.37 times more likely to have hypertension as compared to the age group of 18-24 years, respectively. This was consistent with those studies conducted in Amhara regional state, Ethiopia(62), Dabat HDSS(84), Dabat district and Gondar city (32), Gondar City (33,34), Northern Ethiopia(63), Addis Ababa (40,42,81), Tigray(80), Durame town(38), Wolega(85), Sidama Zone(64, 86), Hawassa University (35), Jimma town (87), Bedele town(88), Dire Dawa city(89), Arba Minch Health and Demographic Surveillance Site(56). Studies conducted in Uganda(68), Cameroon (57,72), Southern Rajasthan(60), South India(59), India (73), China (90), and urban Varanasi(91) also showed that older age was associated with hypertension.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Individuals aged 45-54 years, 55-64 years, and ≥65 years were 4.63, 14.40, and 19.37 times more likely to have hypertension as compared to the age group of 18-24 years, respectively. This was consistent with those studies conducted in Amhara regional state, Ethiopia(62), Dabat HDSS(84), Dabat district and Gondar city (32), Gondar City (33,34), Northern Ethiopia(63), Addis Ababa (40,42,81), Tigray(80), Durame town(38), Wolega(85), Sidama Zone(64, 86), Hawassa University (35), Jimma town (87), Bedele town(88), Dire Dawa city(89), Arba Minch Health and Demographic Surveillance Site(56). Studies conducted in Uganda(68), Cameroon (57,72), Southern Rajasthan(60), South India(59), India (73), China (90), and urban Varanasi(91) also showed that older age was associated with hypertension.…”
Section: Discussionsupporting
confidence: 92%
“…This result was in line with the study conducted in Southern Rajasthan(60). However, studies conducted in urban setting of Ethiopia such as Gondar city (34), Mekelle town(80), Addis Ababa (41,42,81), Durame town (38), Hosanna town(36), and Jigjiga city(82) showed males were at risk for hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood pressure (BP) is the force exerted by circulating blood against the walls of the body’s arteries, the major blood vessels in the body. Hypertension is when blood pressure is too high [ 4 ], while the level of blood pressure is greater than 140/90mmHg in adults aged 18 years or more [ 5 ]. It is commonly termed the silent killer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that the odds of developing hypertension are elevated in those who smoke. Tobacco smoking is associated with increased arterial wall stiffness, thereby increasing the risk of developing hypertension [ 2 ].…”
Section: Discussionmentioning
confidence: 99%